Ireland : Tenth Review Under the Extended Arrangement. (IMF Staff Country Reports; Country Report ;, 2013)
Ireland's strong policy implementation and market conditions have improved macroeconomic indicators to show positive signs. However, an uncertain medium-term outlook could hamper the prospects. Bank supported recovery through timely action on lingering financial sector issues has been identified for sustained growth. Steady progress in fiscal consolidation has to be maintained to support Ireland's durable return to reliance on market financing. Determined policy implementation of strengthened activation policies and SME supports are also required to support growth and contain unemployment.